The Effect of Motivation and Locus of Control on Job Satisfaction and Teacher Performance (Literature Review MSDM) - Lucia Sapto Wendah Wisanti (Dinasti International Journal of Management Science, 2022)
Literature article Reviewing the Effect of Motivation, and Locus of Control on Job Satisfaction and Teacher Performance is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are: 1) Motivation has an effect on Job Satisfaction; 2) Locus of Control has an effect on Job Satisfaction; 3) Motivation has an effect on teacher performance; 4) Locus of Control has an effect on teacher performance; and 5) Job Satisfaction has an effect on teacher performance.